Oregano and lavender essential oils as antioxidant and antimicrobial additives of biogenic gelatin films - Martucci, Josefa Fabiana (2015)
The chemical composition of the essential oils obtained by hydrodistillation from fully-formed, dried oregano leaves (Origanum vulgareOriganum vulgare) and lavender leaves and flowers (Lavandula officinalis) were analyzed by GC/MS. The effectiveness of oregano (OEO) and lavender (LEO) essential oils and a mixture LEO:OEO (50:50) in inhibiting Escherichia coli and Staphylococcus aureus growth were determined. Both essential oils inhibited the growth of the microorganisms tested, being more sensitive to gram-positive bacteria. OEO yielded the lowest values of minimum inhibitory concentration (MICOEO=1600-1800ppm vs. MICLEO=2000ppm against E. coli; MICOEO=800-900ppm vs. MICLEO=1000-1200ppm against S. aureus), due to the higher content of phenolic compound, which also provides antioxidant capacity (IC50OEO=297±89ppm vs. IC50LEO>>6000ppm). Mixture results indicated an antagonist antimicrobial effect between OEO and LEO. Gelatin-based films added with OEO or LEO, were prepared by casting (2000-6000ppm). Mechanical, optical and water vapor barrier properties were determined to observe film functionality. OEO effect on the functional properties of gelatin films was not significant. LEO, in the highest concentration analyzed, promotes a slight change in water vapor permeability of Ge-based films (1.46×10-13 to 6.8×10-14Kg.m/Pa.s.m2), due to its high hydrophobic nature. Oregano containing gelatin films exhibited the highest antimicrobial and antioxidant properties.